A Global Supply Network Design Model: A Resilient Management Approach - Kanchan Das; Adarsh Annand; Mangey Ram (International Journal of Mathematical, Engineering and Management Sciences, 2021)
We propose a design model for creating a resilient supply network applicable for local and global markets. It addresses the ineffectiveness and failure of existing supply network that resulted current economic, food and hospital supply crisis during this ongoing COVID 19 Pandemic situation. The research includes resilience creation approach for the known previously experienced as well as unknown and unforeseen disruption situations. This research considers resilience management-based steps and methods covered in the literature to building abilities of supply networks for absorption, adaptation and recovery for containing disruptions that have severe negative effect on supply chain operations and society. The research studies the options for including SC intermediaries to take the role of supply agent or supply contractors (SCON) to manage supply of items when traditional/classical supply networks known to us were almost inoperative or ineffective to fulfill buyer requirements during this COVID 19 like pandemic situations. A numerical example is solved for illustrating applicability of the model.